2015
DOI: 10.1890/14-0871.1
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi counteract the Janzen‐Connell effect of soil pathogens

Abstract: Soilborne pathogens can contribute to diversity maintenance in tree communities through the Janzen-Connell effect, whereby the pathogenic reduction of seedling performance attenuates with distance from conspecifics. By contrast, arbuscular mycorrhizal fungi (AMF) have been reported to promote seedling performance; however, it is unknown whether this is also distance dependent. Here, we investigate the distance dependence of seedling performance in the presence of both pathogens and AMF. In a subtropical forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 47 publications
8
118
1
Order By: Relevance
“…Although plant communities can strongly shape the habitat conditions for taxa at higher trophic levels 33, 36 , feedback effects of both plant antagonists and mutualists might result in an overall strong top-down control of plant community composition 27, 29 . Our findings are in line with observations in other species-rich forests that have indicated strong effects of soil fungal pathogens, bacteria, and mycorrhizae on plant community composition 2830 . An important role of top-down effects is indicated by strong links between microorganisms and plants in the top-down model that are not found or less evident in the bottom-up model, such as for Alphaproteobacteria and Bacteroidetes.…”
Section: Discussionsupporting
confidence: 92%
“…Although plant communities can strongly shape the habitat conditions for taxa at higher trophic levels 33, 36 , feedback effects of both plant antagonists and mutualists might result in an overall strong top-down control of plant community composition 27, 29 . Our findings are in line with observations in other species-rich forests that have indicated strong effects of soil fungal pathogens, bacteria, and mycorrhizae on plant community composition 2830 . An important role of top-down effects is indicated by strong links between microorganisms and plants in the top-down model that are not found or less evident in the bottom-up model, such as for Alphaproteobacteria and Bacteroidetes.…”
Section: Discussionsupporting
confidence: 92%
“…However, increasing evidence over the last few decades has shown that mycorrhizas can also offer their hosts defence against pathogens (Marx 1972;Maherali and Klironomos 2007;Sikes et al 2009;Wehner et al 2010;Albornoz et al 2016b). They can provide physical barriers around roots against soil-borne pathogens (Marx 1972), produce antimicrobial compounds (Duchesne et al 1988a, b), or neutralise the negative effects of pathogens for seedling survival and growth (Liang et al 2015). In this section, we summarise the current evidence of pathogen defence of both ECM and AM fungi, and discuss their implications for plant-plant interactions in hyperdiverse ecosystems.…”
Section: Nutrient Exchange-based Facilitationmentioning
confidence: 99%
“…Revegetation can provide the biodiversity necessary for recovery of areas impacted by mining. In this context, arbuscular mycorrhizal fungi (AMFGlomeromycota phylum) represent important components of the soil biota that promote diverse services in the ecosystem (Pellegrino;Bedini, 2014), such as better plant nutrition and growth (Thirkell;Cameron;Hodge, 2016), soil aggregation (Leifheit;Verbruggen;Rillig, 2015) and an increase in plant tolerance to biotic stresses (e.g., pathogens) (Liang et al, 2015) and abiotic stresses (e.g., potentially toxic elements in the soil) (Cabral et al, 2015), and assume an important role in the rehabilitation process of areas affected by mining.…”
Section: Introductionmentioning
confidence: 99%